Study of High-cycle Fatigue Properties in Bovine Tibia Bones based on Reliability and Scatter-band Predictions - Mahshad Farzannasab; Mohammad Azadi; Hamed Bahmanabadi (Mechanics of Advanced Composite Structures)
Bones are natural composites, which are consisted of mineral fibers, which strengthen the organic matrix.  Such composites are exposed to both monotonic and cyclic loadings, which could predispose the structure to failure. One such failure mechanism could be the fatigue phenomenon. In this article, the scatter-band and the reliability response of bovine tibia bones were predicted in the load-controlled fatigue condition. The one-point rotary-bending fatigue machine was utilized to carry out standard tests at two different loading levels, 0.4 and 0.6 kg for three various loading frequencies, 10, 20 and 30 Hz for tibia bones. For scatter-band predictions, three confidence levels (85, 90, and 95%) were selected. Addiotionally, lower/upper bands were drawn for a selected target function, including the ratio of logarithmic fatigue lifetimes to stress levels. For the reliability prediction, three different distribution functions were considered. Results showed that, by decreasing the confidence level, the scatter-band would be narrower. Besides, the Probability of failure generally increased at 0.6 kg of the loading level, when the loading frequency increased.